The Effect of Cash Turnover and Receivables Turnover on Profitability in Pharmaceutical Companies - Nastiti Rizky Shiyammurti; Jejen Jaenudin; Rony Wardhana; Budi Prasetiyo; Esti Popi Marceline Zai (CV. Civiliza Publishing, 2025)
Profitability is measured using Return on Assets (ROA) as an indicator of the company's ability to generate profits from total assets owned. Cash turnover shows how efficiently the company manages cash flow in its operations, while receivables turnover shows the company's ability to collect receivables from customers.This study aims to determine the effect of cash turnover and receivables turnover on profitability in pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) during the 2018–2021 period. The research method used is a quantitative method with a descriptive and verification approach. Data were obtained from annual financial reports published by pharmaceutical companies that met the sample criteria. The analysis techniques used include multiple linear regression analysis, classical assumption tests, t-tests for partial testing, and F-tests for simultaneous testing with the help of the SPSS application. The results of the study indicate that cash turnover has a significant effect on profitability, and receivables turnover has a significant effect. Simultaneously, cash turnover and receivables turnover have a significant effect on profitability. This finding confirms the importance of efficient cash and receivables management in supporting the financial performance of pharmaceutical companies.